2013
DOI: 10.1002/mrm.24927
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in MR tracer kinetic parameters and water exchange rates estimated from T1‐weighted dynamic contrast enhanced MRI

Abstract: Purpose The aim of this study was to assess the uncertainty in estimation of MR tracer kinetic parameters and water exchange rates in T1-weighted dynamic contrast enhanced (DCE)-MRI. Methods Simulated DCE-MRI data were used to assess four kinetic models; general kinetic model with a vascular compartment (GKM2), GKM2 combined with the 3S2X model (SSM2), adiabatic approximation of the tissue homogeneity model (ATH), and ATH combined 3S2X model (ATHX). Results In GKM2 and SSM2, increase in transfer constant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…6 Moreover, it is apparent that estimates of the WX-related parameter made using the shutter-speed model (τ i , the intracellular residence time of water) are imprecise. 6,11 Nevertheless, the shutter-speed model has generated considerable interest in the DCE-MRI community, not least because it often fits the data better than the standard 1-compartment Tofts model, 4,12 produces results which may help in the differential diagnosis of breast cancer 5 and yields estimates of an additional parameter, τ i , which, it has been suggested, may reflect important metabolic characteristics of the cells in the tissue imaged. 13 Given the previously highlighted problems, 6 the purpose of this study was 2-fold.…”
Section: Magnetic Resonance In Medicine 1 | Introductionmentioning
confidence: 99%
“…6 Moreover, it is apparent that estimates of the WX-related parameter made using the shutter-speed model (τ i , the intracellular residence time of water) are imprecise. 6,11 Nevertheless, the shutter-speed model has generated considerable interest in the DCE-MRI community, not least because it often fits the data better than the standard 1-compartment Tofts model, 4,12 produces results which may help in the differential diagnosis of breast cancer 5 and yields estimates of an additional parameter, τ i , which, it has been suggested, may reflect important metabolic characteristics of the cells in the tissue imaged. 13 Given the previously highlighted problems, 6 the purpose of this study was 2-fold.…”
Section: Magnetic Resonance In Medicine 1 | Introductionmentioning
confidence: 99%
“…This was based on previous studies that showed that the degree of DCE-MRI data sensitization to the water exchange effect depends on the MRI acquisition protocol, including flip angle. 4,17 Such flip angle dependency is not expected to be observed with other contrast kinetic parameters. Hence, using more than one flip angle in DCE-MRI acquisition may introduce a unique effect of τ i on the timeintensity curve and reduce the uncertainty in τ i estimation.…”
mentioning
confidence: 78%
“…Since there has not been a study, to our best knowledge, that measured all the parameters considered in our study, it was not possible to choose the baseline values from one study. Instead, the baseline values above were selected based on several previous studies . These baseline parameters were used to generate a range of parameters around them (Table ) for the numerical simulation studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations